Staphylococcus aureus contamination in traditional Balinese Indonesian stem food: Tum bungkil, Tum pusuh and Tum biu batu - Kusumaningsih, Purwaningtyas; Puspaningrum, Dylla Hanggaeni Dyah; Dachi, Milafebriani; Mboru, Adriana Dehi (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Tum is a traditional Balinese Indonesian dish made from various parts of the stone banana tree, including the stone banana root bulb (bungkil), stone banana flower (pusuh), and stone banana fruit (biu batu). However, when tum is made by hand without gloves, there is a risk of contamination with Staphylococcus aureus. Although the steaming process may reduce some bacteria, contamination can still occur. S. aureus can survive in ready-to-eat foods prepared under poor hygiene conditions. The toxins produced by S. aureus can lead to skin infections, respiratory problems, and sepsis. This study aims to investigate the presence of S. aureus in processed tum. Purposive sampling was conducted in two districts that sell tum bungkil, pusuh, and biu batu. Six samples were tested using mannitol salt agar (MSA) which is specific media from a dilution level of 10-3. Identification is conducted based on morphology, gram staining and total plate count (TPC) results. The results indicated that the highest level of contamination was found in sample 3 (S3) were 1.7x102CFU/g, which contained tum pusuh. This study implies that it is essential to improve hygiene practices during the preparation of tum pusuh to minimize the risk of contamination.